Relationship between organizational factors and government policy with customer loyalty: a case study of MBSB / Putri Rabiatuladawiyah Othman and Nurul Huda Awang - Othman, Putri Rabiatuladawiyah; Awang, Nurul Huda (2015)
The aim of this study is to find the factors that contribute to the customer loyalty towards Retail Business Division at Malaysia Building Society Berhad (MBSB). The study only focuses on Retail Business Division at MBSB Kuala Terengganu Branch. This research is expected to investigate to what extent the selected independent variables are significant in the study. There are three independent variables in this study which are categorized under internal factors (1) corporate image (2) product and service offered and (3) service personnel. There is one independent variable under external factor. (1) Government rules and regulation. Researcher using primary data to get the information by distribute questionnaire to the respondents. The respondents of this study consist of customers of Retail Business Division at MBSB Kuala Terengganu Branch. Researcher used several analyses to test the data such as Frequencies Analysis, Reliability Analysis, Correlation Analysis, Regression Analysis and Hypotheses Testing. The result of this investigation revealed that all the four selected independent variables are significant in influencing the loyalty of the customers towards Retail Business Division at MBSB Kuala Terengganu Branch. By undertaking this research it can help MBSB to improve their service and product offered and awareness about what actually required by customer hence become top financial institutions in Malaysia.